Traffic Police Investigation System for Traffic Accidents Causing Fatalities (Research Study at Batang Police Traffic Unit) - Widi, Prasetya Nugrahaning; Gunarto, Gunarto (UNISSULA Semarang, 2025)
The police are authorized by law regarding traffic security. Traffic police or called Polantas are implementing elements tasked with carrying out police duties including guarding, regulating, escorting and patrolling, public education and traffic engineering, driver registration and identification, traffic accident investigation and law enforcement in the field of traffic in order to maintain security, order and smooth traffic. Traffic police must conduct investigations into traffic accident cases. The aim of this research is to find out and analyze (1) the implications of positive criminal law on traffic accidents, (2) the investigation scheme by the Traffic Police for traffic accidents with fatalities, (3) the obstacles faced by the Traffic Police in the process of investigating traffic accidents that result in fatalities. The approach method used in this study is sociological juridical. The specifications of this study are descriptive analytical. The data sources used are primary data and secondary data. Primary data is data obtained directly from the field or from the first source and has not been processed by other parties. While secondary data is obtained from library research consisting of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research and discussion, it can be concluded: (1) In Article 229 of Law Number 22 of 2009 concerning Traffic and Road Transportation, traffic accidents are classified into three, namely minor traffic accidents, which are accidents that result in damage to vehicles and/or goods; moderate traffic accidents, which are accidents that result in minor injuries and damage to vehicles and/or goods; serious traffic accidents, which are accidents that result in victims dying or being seriously injured. (2) The Traffic Police Scheme in investigating traffic accidents that result in victims dying is to process reports/information; visit the Scene of the Crime; request for a Visum et Repertum and evidence in the case of accident victims who die or to take them to the hospital to carry out a Visum et Repertum or treatment by the Traffic Police with the support of operational Ambulance vehicles to speed up the evacuation process. (3) In the investigation process of the accident case, there are obstacles faced by the Police Traffic Unit, these obstacles include weak evidence. Strong evidence can be in the form of eyewitness statements, CCTV recordings, photos or videos of the incident, medical records, or other documents that can prove the perpetrator's involvement in the accident. However, if the evidence produced is not strong enough or too little, the court may not be able to consider the case.